Lecturers’ Competences towards 21st-Century Learning Transformation and the Challenges of Industrial Revolution 5.0 - Ummul Khair; Kholik (Corolla International Conference, 2023)
Teachers and lecturers are important components in preparing the younger generation for the future, which is the hope of the nation. In order to produce professional lecturers with qualified competencies to face the challenges of the industrial revolution 5.0, Society 5.0, which is a new future for humans that relies on the advanced use of technology in various aspects of life, including Industry 4.0 and cybernics, must be considered. The vision of Society 5.0 demands a transformation in learning. Therefore, this paper will explain Society 5.0 and the importance of educational transformation, 21st-century learning and its implications for lecturers, and the development of literacy competencies and efforts to strengthen the education system.